Company Profile Book Design Training for UMKM the Convection and Computer Embroidery Industry by CV. Sinar Surya Mustika, Surabaya - Widyasari; Sri Wulandari; Samuel Rihi Hadi Utomo; Ramadhani Putra Viadianto; Hafidz Arya Wijaya (Nusantara Science and Technology Proceedings, 2022)
Globalization requires people to be more creative in seeing opportunities and making the most of them by paying attention to sustainability factors. The era of globalization which is full of demands like today, also requires people to continue to be able to meet complex needs, not only household needs but also needs related to food, clothing, transportation, and so on. One solution to this problem is to create jobs independently, not just being a job seeker. Job creation can be in various forms, one of which is through Micro, Small, and Medium Enterprises (UMKM). UMKM is expected to be able to become the pillar of the national economy with an insight into independence and has great potential to improve people's welfare. CV. Sinar Surya Mustika is a UMKM that was established in 2020 in Surabaya and is engaged in the convection and computer embroidery industry. Through observations and interviews with Mr. Moch. Taqiyuddin Abror is the owner of UMKM computer convection and embroidery industry by CV. Sinar Surya Mustika, his convection and embroidery industry always prioritizes the best services and solutions for consumer needs, provides quality and innovative results, and implements strict quality control at every stage. However, in the marketing aspect, CV. Sinar Mustika has limitations, especially in digital marketing. This is due to the lack of human resources who master digital marketing. The company profile book design training is expected to increase digitally literate human resources so that the market reach becomes wider, easier, and more effective. The design of the company profile book can be a marketing tool for a CV. Sinar Surya Mustika is facing a high level of competition in the era of globalization. This training is based on community service activities by providing training on company profile book design for UMKM Convection and Computer Embroidery Industry by CV. Sinar Surya Mustika, Surabaya. This community service activity is based on an audience study. The methods used during the activities include presentation, demonstration and practice methods. The results achieved in this outreach activity were providing information and knowledge about the company profile design, discussions with UMKM Convection and Computer Embroidery Industry by CV. Sinar Surya Mustika and design a company profile book.